1999
DOI: 10.1210/jc.84.10.3770
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Low Density Lipoprotein from Insulin-Dependent Diabetic Patients on Platelet Functions

Abstract: In the present work we studied in vitro the action of low density lipoproteins (LDL) isolated from normolipemic insulin-dependent diabetic (IDDM) patients on transmembrane cation transport, nitric oxide synthase (NOS) activity, and aggregating response to stimuli of platelets from healthy subjects to elucidate whether the modified interaction between circulating lipoproteins and cells might be one of the pathogenetic mechanisms of the increased platelet activation in IDDM. LDL were obtained by discontinuous gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…increased fluidity of the membrane. This phenomenon can result either from increased phospholipids or increased unsaturated fatty acid content [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…increased fluidity of the membrane. This phenomenon can result either from increased phospholipids or increased unsaturated fatty acid content [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The mean values of LPC range between 2 and 5% LPC of total LDL phospholipids in most of the recent studies [65,66] (Corrinth and Siess, unpublished observations). LPC increases 2-10-fold dependent on the degree of LDL oxidation.…”
Section: Lpc Formation During Oxidation Of Ldlmentioning
confidence: 89%
“…In a recent study, however, it has been observed that LDL isolated from insulin-dependent diabetic patients had a significant higher LPC content (9.62 8 2.04% of LDL phospholipids) as compared to LDL of healthy controls (4.55 8 1.86% of LDL phospholipids). The LDL of diabetic patients increased cytosolic Ca 2+ concentrations and potentiated ADP-induced aggregation [65] . Whether this effect was due to the increased LPC content of LDL of diabetic patients or other mechanisms, remains an open question.…”
Section: Action Of Lpc On Plateletsmentioning
confidence: 95%
“…Stimulation of PAF receptor decreased Na-K ATPase in rat proximal tubule contributing to natriuresis (Handa et al, 2003). In in vitro study of platelet incubated with LDL, IDDM LDL significantly increased platelet aggregation and significantly reduced platelet membrane Na-K ATPase compared with control LDL (Rabini et al, 1999). …”
Section: Introductionmentioning
confidence: 99%
“…Na-K ATPase acts on Na reabsorption in distal tubule and collecting duct of kidney cell. Na-K ATPase is reduced in patients with insulin resistant diabetes, obesity and hypertension (Hakam et al, 2006; Rabini et al, 1999). Angiotensin receptor agonists inhibit proximal tubule Na-K ATPase in obese hypertensive rat and Na induced hypertension was accelerated with taurine deficiency (Hakam et al, 2006).…”
Section: Introductionmentioning
confidence: 99%